Nitrogen acquisition strategy shifts with tree age depending on root functional traits and soil properties in Larix principis-rupprechtii plantations - Liu, Qianyuan; Chen, Yaxuan; Chen, Yanmei (Frontiers in Plant Science, 2024)
Variation in plant nitrogen uptake rate and substrate preference is complicated due to the combined influence of abiotic and biotic factors. For the same species of tree across different ages, the interactions between root structural traits, nitrogen uptake rate, and soil environment have not been fully characterized, a situation that constrains our understanding of underground resource strategies employed by trees at different ages. In the present study, we examined the nitrogen uptake rate, mycorrhiza, morphology, architecture, and chemistry of the roots of Larix principis-rupprechtii in a chronosequence (aged 18, 27, 37, 46, and 57 years) in the Saihanba Mechanical Forest Farm in Northern China. L. principis-rupprechtii preferred to absorb ammonium, followed in order by glycine and nitrate. The ammonium uptake rate of L. principis-rupprechtii significantly decreased (aged 18-37 years) and then increased (aged 46-57 years) with tree age. The glycine, nitrate, and total nitrogen uptake rates decreased with tree age. The root resource acquisition strategy appeared to shift from 2 an acquisitive strategy to a conservative strategy associated with increasing tree age.Along the root-mycorrhizal collaboration gradient, the younger L. principisrupprechtii relied more on their own root morphology and physiology to acquire resources, adopting a "do it yourself" strategy comprising increasing the specific root length, the specific root area, and the N uptake rate (nitrate and glycine). Conversely, older trees depended more on mycorrhizal partners to acquire nitrogen resources, an "outsourcing" strategy. The results contribute to our understanding of underground resource-use strategies of plants and the nitrogen cycle in forest ecosystems according to stand age.